CD73 on T Cells Orchestrates Cardiac Wound Healing After Myocardial Infarction by Purinergic Metabolic Reprogramming. Issue 3 (18th July 2017) - Borg, Nadine; Alter, Christina; Görldt, Nicole; Jacoby, Christoph; Ding, Zhaoping; Steckel, Bodo; Quast, Christine; Bönner, Florian; Friebe, Daniela; Temme, Sebastian; Flögel, Ulrich; Schrader, Jürgen
Abstract : Background: T cells are required for proper healing after myocardial infarction. The mechanism of their beneficial action, however, is unknown. The proinflammatory danger signal ATP, released from damaged cells, is degraded by the ectonucleotidases CD39 and CD73 to the anti-inflammatory mediator adenosine. Here, we investigate the contribution of CD73-derived adenosine produced by T cells to cardiac remodeling after ischemia/reperfusion and define its mechanism of action. Methods: Myocardial ischemia (50 minutes followed by reperfusion) was induced in global CD73 −/− and CD4-CD73 − /− mice. Tissue injury, T-cell purinergic signaling, cytokines, and cardiac function (magnetic resonance tomography at 9.4 T over 4 weeks) were analyzed. Results: Changes in functional parameters of CD4-CD73 −/− mice were identical to those in global CD73 knockouts (KOs). T cells infiltrating the injured heart significantly upregulated at the gene (quantitative polymerase chain reaction) and protein (enzymatic activity) levels critical transporters and enzymes (connexin43, connexin37, pannexin-1, equilibrative nucleoside transporter 1, CD39, CD73, ecto-nucleotide pyrophosphatase/phosphodiesterases 1 and 3, CD157, CD38) for the accelerated release and hydrolysis of ATP, cAMP, AMP, and NAD to adenosine. It is surprising that a lack of CD39 on T cells (from CD39 −/− mice) did not alter ATP hydrolysis and very likely involves pyrophosphatases (ecto-nucleotide pyrophosphatase/phosphodiesterases 1 and 3). Circulating T cells predominantly expressed A2a receptor (A2a R) transcripts. After myocardial infarction, A2b receptor (A2b R) transcription was induced in both T cells and myeloid cells in the heart. Thus, A2a R and A2b R signaling may contribute to myocardial responses after myocardial infarction. In the case of T cells, this was associated with an accelerated secretion of proinflammatory and profibrotic cytokines (interleukin-2, interferon-γ, and interleukin-17) when CD73 was lacking. Cytokine production by T cells from peripheral lymph nodes was inhibited by A2a R activation (CGS-21680). The A2b R agonist BAY 60-6583 showed off-target effects. The adenosine receptor agonist NECA inhibited interferon-γ and stimulated interleukin-6 production, each of which was antagonized by a specific A2b R antagonist (PSB-603). Conclusions: This work demonstrates that CD73 on T cells plays a crucial role in the cardiac wound healing process after myocardial infarction. The underlying mechanism involves a profound increase in the hydrolysis of ATP/NAD and AMP, resulting primarily from the upregulation of pyrophosphatases and CD73. We also define A2b R/A2a R–mediated autacoid feedback inhibition of proinflammatory/profibrotic cytokines by T cell–derived CD73. Abstract : Supplemental Digital Content is available in the text.